1987
DOI: 10.1111/j.1365-2672.1987.tb02415.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of rats associated with a human faecal flora as a model for studying the effects of diet on the human gut microflora

Abstract: The activities of four bacterial biotransformation enzymes (beta-glucosidase, beta-glucuronidase, nitrate reductase and nitroreductase) were measured in the caecal contents of conventional flora rats or germ-free rats contaminated with a mixed, human faecal flora and compared with activities present in a fresh human stool preparation. Both the conventional flora rats and the rats inoculated with a human flora exhibited an enzyme profile generally similar to that of human faeces, although the conventional rat f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 19 publications
(12 reference statements)
1
53
1
2
Order By: Relevance
“…As cefquinome is mainly used in pigs, and because the intestinal flora is very different between rats and pigs, we used a model of gnotobiotic rats harboring porcine fecal flora samples enriched with a CTX-R E. coli strain. Indeed, it has been shown that the implanted flora were stable and comparable to natural flora from the sampled individuals (24,25). No measurable enrichment of CTX-R Enterobacteriaceae was observed with the prepatent phase adjusted dose, whereas rapid and massive amplification of CTX-R Enterobacteriaceae was observed with the patent phase adjusted dose.…”
Section: Discussionmentioning
confidence: 96%
“…As cefquinome is mainly used in pigs, and because the intestinal flora is very different between rats and pigs, we used a model of gnotobiotic rats harboring porcine fecal flora samples enriched with a CTX-R E. coli strain. Indeed, it has been shown that the implanted flora were stable and comparable to natural flora from the sampled individuals (24,25). No measurable enrichment of CTX-R Enterobacteriaceae was observed with the prepatent phase adjusted dose, whereas rapid and massive amplification of CTX-R Enterobacteriaceae was observed with the patent phase adjusted dose.…”
Section: Discussionmentioning
confidence: 96%
“…Molecular techniques that do not require isolation of bacterial strains, such as ERIC-PCR fingerprinting, TGGE/denaturing gradient gel electrophoresis (DGGE) analysis, 16S rRNA gene clone library profiling and real-time PCR, were utilized to analyze the microbiota in the gut of the HFA piglets. Previous studies on the microbiota composition of HFA animals were based on traditional culture methods (Raibaud et al, 1980;Hazenberg et al, 1981;Mallett et al, 1987;Hirayama, 1999), which underestimate the abundance of the bacterial populations and thus provide an incomplete picture of the composition of the microflora. Use of the abovementioned molecular methods will yield more detailed information about the microbiota and will provide a more comprehensive comparison of the microbiota in the HFA animals and the human donor.…”
Section: Resultsmentioning
confidence: 99%
“…HUM mice (ex-GF mice colonized with a human microbiota) are emerging as a powerful model for studying humanrelevant microbes in a controlled experimental setting (Mallett et al, 1987;Bowey et al, 2003). Here we use HUM mice as a model for studying metabolomic changes within urine and feces.…”
Section: Introductionmentioning
confidence: 99%